Continuity and Change of Religious Affiliation in Contexts of Rapid Transformations: The Chilean 1938–1963 Generation (2024)
This article explores the religious trajectories of individuals born between 1938 and 1963 in Santiago, Chile, a generation that witnessed significant social and political transformations. Using survey data and a life history calendar from a representative sample of 792 individuals, we applied descriptive statistics, sequence analysis, and logit multivariate models to assess the factors driving religious persistence and change over their lifetimes. Chile provides a unique case study of Evangelical and Pentecostal growth due to the rapid expansion of these movements during the 1960s and 1970s. We examine the role of economic modernization and family religious transmission in shaping religious identification. Our findings reveal limited religious pluralism within a broader framework of stability: religious identities formed in youth remained relatively fixed, with some conversions to Evangelism from Catholicism later in life. These results challenge two common assumptions in the literature: that religious identity is primarily fixed in childhood, and that all Chilean cohorts have experienced steady secularization in recent decades.